A conceptual study of business orientations and its effect on strategic planning in small businesses. - Lee, Darren Cheng Loong. (2012)
This paper strives to understand the relationship between Market Orientation, Learning Orientation and Strategic Planning in the context of small businesses. All of these three areas have been studied extensively due to their proven direct bearings on business performance. We propose a conceptual model to reconcile them by positing that Market Orientation and Learning Orientation can have an influence on a small firm’s planning process. We also analyse the possibility that deductions be drawn on a firm’s planning process through knowledge of her business orientations. Additional research will need to be done in order to validate the scales used and the theories proposed. This paper suggests the use of Structured Equation Modelling for this purpose.